Courier delivery services visualisor (CDSV) with an integration of genetic algorithm and A* engine - Jalaluddin, Mohammad Fariduddin; Kamaru-Zaman, Ezzatul Akmal; Abdul Rahman, Shuzlina; Mutalib, Sofianita (2017)
Online shopping has become one of the popular mediums for people to use online transactions due to its economical and easiness.It is more convenient to those who simply do not have time to shop physically and prefer delivery service. However, the courier services nowadays are unable to keep up with the increasing consumer demand. The problem is caused by the delivery process that is not synchronized due to the problem of finding the best route of distribution. Distributors are unable to plan their distribution path with the minimal distance.Furthermore distributors are only able to reach each district distribution centre once a day and revisit the distribution centre will increase the time spent and operation cost. This study developed Courier Delivery Services Visualisor (CDSV) that is able to visualize the best route to be taken by distributor, so that the courier service can arrive on time.CDSV employed Genetic Algorithm (GA) and Astar Algorithm (A*) that integrates with Geographical Information System (GIS) data.A graphical user interface in the form of simulation map that suggests the best route and the optimal distance are displayed for easier courier service distribution references.